Basal ganglia neuronal activity during scanning eye movements in Parkinson's disease - Sieger, Tomáš; Bonnet, Cecilia; Serranová, Tereza; Wild, Jiří; Novák, Daniel; Růžička, Filip; Urgošík, Dušan; Růžička, Evžen; Gaymard, Bertrand; Jech, Robert (PloS one, 2013)
The oculomotor role of the basal ganglia has been supported by extensive evidence, although their role in scanning eye movements is poorly understood. Nineteen Parkinsońs disease patients, which underwent implantation of deep brain stimulation electrodes, were investigated with simultaneous intraoperative microelectrode recordings and single channel electrooculography in a scanning eye movement task by viewing a series of colored pictures selected from the International Affective Picture System. Four patients additionally underwent a visually guided saccade task. Microelectrode recordings were analyzed selectively from the subthalamic nucleus, substantia nigra pars reticulata and from the globus pallidus by the WaveClus program which allowed for detection and sorting of individual neurons. The relationship between neuronal firing rate and eye movements was studied by crosscorrelation analysis. Out of 183 neurons that were detected, 130 were found in the subthalamic nucleus, 30 in the substantia nigra and 23 in the globus pallidus. Twenty percent of the neurons in each of these structures showed eye movement-related activity. Neurons related to scanning eye movements were mostly unrelated to the visually guided saccades. We conclude that a relatively large number of basal ganglia neurons are involved in eye motion control. Surprisingly, neurons related to scanning eye movements differed from neurons activated during saccades suggesting functional specialization and segregation of both systems for eye movement control.
Keywords: dospělí; Deep Brain Stimulation; pohyby očí; Female; Eye Movements; globus pallidus; Parkinsonova nemoc; Antiparkinson Agents; Electrodes, Implanted; Levodopa; Brain Mapping; levodopa; Adult; ženské pohlaví; lidé; rozpoznávání obrazu; neurony; bazální ganglia; Globus Pallidus; mapování mozku; Subthalamic Nucleus; Neurons; antiparkinsonika; Male; Aged; nucleus subthalamicus; Reading; hluboká mozková stimulace; Pattern Recognition, Visual; implantované elektrody; Basal Ganglia; Microelectrodes; lidé středního věku; Substantia Nigra; mikroelektrody; senioři; mužské pohlaví; substantia nigra; čtení; Middle Aged; Parkinson Disease; Humans